Software Reliability Testing Tools: An Overview and Comparison (International Journal of Engineering and Computer Science, 2016)
Software reliability has been regarded as major quality attribute and still there are very few available standardized tools. Software reliability is such a significant factor in finalizing the overall quality of software, thus it must be estimated. In this paper we will discuss various software reliability metrics. A well designed metrics can helps in detection and correction of requirement faults that will guide in avoidance of error in later stage of software development.  A software reliability growth model is one of the basic techniques used to evaluate the software reliability quantitatively. The software growth model is required to have a significant performance in term of goodness of fit, reliability etc. In this paper we will summarize some existing software reliability tools such as CASRE, SMERFS, SOFTREL, SOREL etc. Overall the paper will provide various ways to enhance software reliability.